Air Pollution and the Labor Market: Evidence from Wildfire Smoke - Mark Borgschulte; David Molitor; Eric Yongchen Zou (Institute of Labor Economics (IZA), 2022)
We study how air pollution impacts the U.S. labor market by analyzing effects of drifting wildfire smoke that can affect populations far from the fires themselves. We link satellite smoke plume with labor market outcomes to estimate that an additional day of smoke exposure reduces quarterly earnings by about 0.1 percent. Extensive margin responses, including employment reductions and labor force exits, can explain 13 percent of the overall earnings losses. The implied welfare cost of lost earnings due to air pollution exposure is on par with standard valuations of the mortality burden. The findings suggest that labor market channels warrant greater consideration in policy responses to air pollution.
Keywords: J21; Q51; Q52; Q53; Q54; 330; air pollution; labor market; wildfires